Landforms, loops, and loess: the Southern Odenwald and the Lower River Neckar valley - Mächtle, Bertil; Bubenzer, Olaf (Landscapes and landforms of Germany, 2025)
Most of the southern Odenwald region is characterized by an overall flat topography, formed in the Triassic Buntsandstein, that is dissected deeply by the lower River Neckar and its tributaries. The region experienced a complex history of uplift, tilting, and formation of a scarpland. Tectonic activity and Pleistocene climate dynamics forced the river Neckar to incise deep valley meanders, with distinct undercut and slip-off slopes and frequently to leave its bed to form a number of incision levels and loop branches. On the slopes, periglacial cover beds smooth the terrain. As a special feature, the Cretaceous remnant of the Katzenbuckel Volcano close to Eberbach is enthroned above the Buntsandstein Plateau where several former loops with five cut-off spurs of the river Neckar are incised. Downstream, the former Mauer loop represents the scenery for the activity of Homo heidelbergensis ca. 600 000 years ago. Close to Heidelberg, the Pleistocene loess sequence of the Haarlass site represents no less than the locus classicus for loess research. To the north, the dissected Crystalline Odenwald has its own specific shape. A train trip provides a good opportunity to experience the beauty and complexity of landforms along the river Neckar and the “Naturpark Neckartal-Odenwald” with numerous educational trails.
Gesehen am 18.02.2026